Book Review of Why Am I Tolerating Christians?: Religious Tolerance Among Confucian Scholars in Mid-Nineteenth-Century China - CAI, Yizhen (Journal of Research for Christianity in China (JRCC), 2024)
Kong Dewei, Why Do I Tolerate Christians? Religious Tolerance Among Confucian Scholars in Mid-19th Century China. Taipei: ShowWe Information Technology Co., Ltd., 2009. 290 pp. NT80.